Productivity change in the CEE commercial banks during a period of restricted bank regulation and stable economic growth - Igor Stubelj; Aleš Trunk; Barbara Švagan; Suzana Laporšek (Economies, 2023)
The paper studies the productivity change of the commercial banks in the CEE countries over the post-crisis period 2013-2018. The productivity change is measured by the Malmquist Productivity Index and its sub-components, applying two approaches-the asset-oriented and profit-oriented intermediation approaches. The analysis uses data from a balanced panel of 181 commercial banks in 11 CEE countries. We find that commercial banks' productivity, measured with the asset-oriented intermediation approach, decreased in most of the CEE countries over 2013-2018, with a decline ranging, on average, from 1% to 6.9%, driven mainly by a decline in technical efficiency. Nevertheless, estimates using the profit-intermediation approach point to productivity growth in commercial banks in all CEE countries, ranging, on average, from 0.5% to 6.3%. The empirical findings imply the need for the CEE commercial banks to further digital transformation and cost rationalization.
Keywords: 330; commercial banks; productivity; productivity change; Malmquist index; Central andEastern Europe